The Relationship between Self Efficacy and Anxiety in Chronic Kidney Failure Patients Undergoing Hemodialysis at Prof. Dr. H. Aloei Saboe Hospital - Vangly Runtuwene; Fadli Syamsuddin; Nikmawati Puluhulawa (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Patients with chronic kidney disease undergoing hemodialysis commonly experience anxiety due to the long-term treatment process and uncertainty regarding their health conditions. One important factor influencing anxiety levels is self-efficacy, which refers to an individual’s confidence in their ability to manage difficult situations. High self-efficacy is believed to reduce anxiety and improve patients’ ability to undergo treatment effectively. Objective: To determine the relationship between self-efficacy and anxiety among patients with chronic kidney disease undergoing hemodialysis at Prof. Dr. H. Aloei Saboe Hospital. Methods: This study used a quantitative approach with a cross-sectional design. The sample consisted of 58 respondents selected using purposive sampling techniques. Data were collected using the Chronic Kidney Disease Self-Efficacy (CKD-SE) questionnaire and the Hamilton Anxiety Rating Scale (HARS). Data analysis was performed using univariate and bivariate analyses with correlation tests. Results: The findings showed that most patients with high self-efficacy experienced low levels of anxiety, whereas patients with low self-efficacy tended to experience moderate to severe anxiety. Statistical test results showed a p-value of 0.000 (p < 0.05), indicating a significant relationship between self-efficacy and anxiety. Conclusion: There was a significant relationship between self-efficacy and anxiety among patients with chronic kidney disease undergoing hemodialysis. Improving self-efficacy is important in helping reduce patient anxiety. Suggestion: This study is expected to serve as a basis for nursing interventions aimed at improving self-efficacy among patients with chronic kidney disease, as well as providing appropriate education and psychological support during hemodialysis treatment.